An influence of organizational culture and organizational commitment on sales officer performance - Meilia Krisanti; Iskandarini, Iskandarini; Linda Trimurni Mass (SEAN Institute, 2024)
Poor organizational performance will make it difficult for the organization or company to satisfy consumers, which of course will hurt profits, company reputation, and sales. Meanwhile, high performance can help companies achieve consistently high goals and results over time. This research aims to analyze the influence of organizational culture and organizational commitment on the performance of PT sales officers. Medan Branch State Savings Bank. Type of quantitative research. Data collection techniques use questionnaires, observation, and documentation. The sample consisted of 58 respondents. The sampling technique is total sampling. Data analysis uses multiple regression. The research results show that organizational culture influences the performance of sales officers where the sig value is 0.000 < 0.05. Organizational commitment influences the performance of sales officers where the sig value is 0.000 < 0.05.